Parenting Practices and Behavioral Problems among Adolescents’ of Parents with Psychopathology: Role of Adolescents’ Coping as Moderator” - Sabih, Fazaila; ul Haque, Anis; Younas, Sana; Mushtaq, Asia (Technium Social Sciences Journal, 2021)
Numerous studies suggest that symptoms of mental illness in parents become reflected in family and parent–child interactions, affecting the nature and quality of caregiving and, in turn, both short- and long-term child outcomes. Given the paucity of research in this area in Pakistan, present study aims to examine differences in parenting practices and behavioral problems among adolescent children of parents with psychopathology and without psychopathology. It also explores moderating role of adolescents’ coping on the relationship between parenting practices and behavioral problems. Sample included 348 parents and their adolescent children divided into two groups: Parents with Psychopathology and without Psychopathology. Alabama Parenting Questionnaire, Youth Self Report, and Brief COPE were used for data collection. Results indicated that adolescent children having parents with psychopathology have elevated levels of behavioral problems as compared to adolescent children of parents without psychopathology. Results of moderation analyses revealed that problem-focused coping, positive coping, and religious coping mitigated the potential impact of negative parenting practices on externalizing problems whereas denial exacerbated this relationship. The implications are discussed for implementation of effective preventive interventions with at risk families and children.